Assurance practices in Colombia’s non-financial sectors: enhancing sustainability report reliability (2024)
This research enhances the reliability of sustainability reports in Colombia’s mining–hydrocarbons, construction, and manufacturing sectors. Amid growing demands for corporate transparency, this study evaluates assurance practices and proposes a model for measuring sustainability report reliability. Using bootstrapping regression, this study provides credible coefficient estimates without assuming a normal distribution. Key findings show that SDG application, assurance scope, and auditing firm consistency significantly influence report reliability, affirmed by 95% confidence intervals. This study’s pragmatic approach suggests best-case and worst-case scenarios for policymakers and companies to optimize report reliability. Furthermore, the proposed model paves the way for future research, with the International Standard on Sustainability Assurance (ISSA) 5000 by the International Auditing and Assurance Board (IAASB), potentially acting as a catalyst for mandatory sustainability reporting in Latin America. This proposed standard promises to enhance sustainability assurance practices. This research contributes to academic discourse on sustainability assurance and guides improvements in corporate reporting transparency and accountability. Future research should expand this model to other sectors and regions, validating its applicability and exploring broader temporal scopes to strengthen its empirical foundations